The mediating role of market value to company dynamic performance - Dewi Nari Ratih Permada; Ananda Sabil Hussein; Risna Wijayanti; Kusuma Ratnawati (Global Business & Finance Review (GBFR), 2024)
Purpose: This study examines the performance of 35 Indonesian Consumer Non-Cyclical Companies through fixed asset, cost of goods sold, and operating expenses as independent variables and market value as mediating variable to company dynamic performance. Design/methodology/approach: Dynamic performance describes how much the company's ability to compre-hensively processing their business (fixed assets (FA), operational expense (OE) and cost of goods sold(COGS)) to produce value which signalled the market as market value or capitalization. Data envelopment analysis (DEA) used to produce numerical data for FA, OE, and COGS. The data collected through company's annual report for 14 years. Findings: Our data suggest that all of company inputs such as fixed assets, operational expenses and cost of goods sold have a negative path coefficient to Dynamic Performance. Data suggest that the more productive a company, the smaller its dynamic performance. Moreover, the higher the market value of a company, the smaller the company dynamic performance. Simultaneously, mediating role of more likely it is to has the effect of reducing company dynamic performance. Research limitations/implications: The mediating variable in this study is market value which is not related to the input variables in this study. For further research, it can use moderating variables related to investment risk, profit projections, economic growth, and public policy because macro things are more visible in the company's operations in the eyes of stakeholders. Originality/value: This research provides a new understanding related to efficiency, where efficiency is not necessa-rily generated from a series of production processes, but it needs to be observed that certain values of each input variable can produce a negative relationship to the achievement of dynamic performance.
Keywords: 650; Consumer Non-Cyclical Companies; dynamic performance; market value; production capabilities